Pengaruh Kompetensi Pedagogik Guru PAK terhadap Kedisiplinan Peserta Didik Kelas V SD Negeri 1 Pardomuan 1 Pangururan Kecamatan Pangururan Kabupaten Samosir Tahun Pelajaran 2023/2024 - Eyani Sisilia Simbolon; Frainskoy Rio Naibaho; Mariyska Debora Silalahi (Jurnal Budi Pekerti Agama Kristen dan Katolik, 2024)
The purpose of this study was to determine the positive and significant influence between PAK Teacher Pedagogical Competence on Student Discipline of Class V SD Negeri 1 Pardomuan 1 Pangururan, Pangururan District, Samosir Regency in the 2023/2024 Academic Year. The method used is a quantitative research method, with a population of 45 students, the sample of this study was 45 students so it is called population research. The instrument used in this study used a closed questionnaire of 42 statement items, where 27 questionnaire items were for variable X and 15 items for variable Y which had been tested on 30 students. The results of the study showed a positive and significant influence between PAK Teacher Pedagogical Competence on Student Discipline of Class V SD Negeri 1 Pardomuan 1 Pangururan, Pangururan District, Samosir Regency in the 2023/2024 Academic Year. 1) Test of the relationship rcount> rtable, namely 0.632> 0.294; 2) Significant test tcount>ttable which is 5.348>2.021; 3) Determination test is 39.94%, 4) Regression equation is obtained from Y ̂ = "15.56" + 0.41X; 5) Hypothesis test using F test obtained Fcount>Ftable = (α = 0.05, dk numerator k = 19, dk denominator = n-2 = 45-2 = 43) which is 28.45> 1.51. Thus Ha, namely there is a positive and significant influence between Pedagogical Competence of PAK Teachers on the Discipline of Class V Students of SD Negeri 1 Pardomuan 1 Pangururan, Pangururan District, Samosir Regency in the 2023/2024 Academic Year is accepted and H0 is rejected.